Uji Komperatif Efektivitas Isometric Handgrip Exercise Dan Slow Deep Brething Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Kelurahan Simpang Selayang - Jenpina Sitepu; Lenny Lusia Simatupang (PT. Hasba Edukasi Mandiri, 2025)
High blood pressure, or hypertension, is a persistent abnormal increase in blood pressure in the arteries with systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Hypertension can cause death, and damage to the heart, brain, and kidneys. One of the non-pharmacological treatments for hypertension is Isometric Hangdrip Exercise, Slow Deep Breathing. The purpose of this study was to see the effect of isometric handgrip exercise and slow deep breathing on reducing blood pressure in hypertensive patients. The method used a quasi-experimental design or also called Quasi Experimental with one group pretest-posttest design. The sample size selected using the Total sampling technique was 28 respondents. The the parametric Paired Sample T-test and the comparative test using the parametric Independent T-test. The results of study research show that there is a significant effect between isometric handgrip exercise and slow deep breathing on decreasing blood pressure with a p-value of (0.001) < (0.005) for isometric handgrip exercise and (0.003) < (0.005) for Slow Deep Breathing and a comparative test with a value of 0.37> α (0.05). It is recommended for further researchers to be able to increase the research sample, combine both interventions, and research respondents with grade I hypertension.